The impact of peer support on testing, linkage to and engagement in HIV care for people who inject drugs in Indonesia: qualitative perspectives from a community-led study - Arif Rachman Iryawan; Claudia Stoicescu; Faisyal Sjahrial; Kuntanto Nio; Alexa Dominich (BMC, 2022)
Abstract Introduction People who use, including those who inject, drugs in Indonesia are disproportionately affected by HIV, but tend to be diagnosed at a late stage of infection, delay initiation to and have poor rates of retention in antiretroviral treatment, resulting in high rates of morbidity and mortality. In addition to legal, policy and health system barriers, PWID may be hesitant to engage in HIV, treatment and care due to lack of knowledge, distrust of the health care system, and stigma related to their dual drug use and HIV status. Implementation of formal peer support initiatives may reduce provider- and individual-level barriers and increase testing, linkage to, and engagement in HIV care among people who use drugs. Methods We conducted a community-led qualitative study to explore the impacts of peer support for people who inject drugs on HIV care access and engagement in Indonesia. Semi-structured, in-depth interviews were conducted with 20 participants in Jakarta and Bandung. Thematic analysis was used to explore how people who inject drugs living with HIV (PWID LHIV) (n = 8), peer support workers (n = 6), and service providers (n = 6) perceived peer support provision by non-governmental organisations. Results Participants unanimously described peer support as beneficial. Peer support workers were widely credited with facilitating access to HIV testing, referral to care, uptake of and adherence to antiretroviral treatment, as well as sustaining engagement in care for PWID. Support mechanisms that facilitated positive peer experiences included provision of HIV knowledge and awareness, emotional support, help with navigating complex bureaucracy, developing trust in health care services, enhancing confidence and motivation, and supporting peers to navigate a wide range of health and social welfare services beyond HIV-related care. Conclusions Findings indicate that peer support can enhance access to testing, linkage to, and engagement in HIV care for people who use drugs living with HIV in Indonesia. In a context of an ongoing HIV epidemic among people who use drugs, reduced funding and policy attention to HIV and harm reduction, there is an urgent need to prioritize peer support interventions to identify people who use drugs facing health risks and link them to appropriate services.